الموازنة بين المقدمتين الطلية والخمرية - عمراوي, مكية (كلية الأدب العربي والفنون, 2024)
تهدف هذه الدراسة إلى إستجلاء بعض مظاهر الموازنة في المقدمة الطللية والخمرية، واستنباط ايحائتها ورموزهما، والبحث في معانيهما، واستنطاقهما، للكشف عن جوانب الإبداع والاختلاف فيهما. أما المحاور الأساسية لهذه الدراسة فهي: توضيح مفهوم الطّلل والخمر وبيان موضوعاتهما والبحث عن دلالاتهما في الوقعة الطللية والخمريات، إضافة إلى تحديد مفهوم المقدمة الشعرية عند النقاد القدامى والمحدثين وأقسامها المتعدَّدَةِ. ومن ثُمَّ تبيان تجلياتهما في القصائد الطللية والخمرية بعرض نماذج مختلفة للشاعرين. وكشفت هذه الدراسة عن الكثير من النتائج، أهمها: اكتساب الطّلل والخمر رمزية دلالته عبّر عنها الشاعرين بمعان ذاتية تخفي في ثناياهما أسرار اخفيّة، ورؤى إبداعية - وآفاقًا جمالية. والقدرة على شحن اللّغة، فكانت الصّور الشّعرية مفحمة بالخيال الذي أمدّها بطاقة إيحائية This study aims to clarify some aspects of the balance in the introduction of the ruins and wine, and to deduce their connotations and symbols, and to search for their meanings, and to interrogate them, to reveal the aspects of creativity and difference in them. The main axes of this study are: clarifying the concept of the ruins and wine, explaining their topics, and searching for their connotations in the incident of the ruins and wine poems, in addition to defining the concept of the poetic introduction among ancient and modern critics and its various sections. Then clarifying their manifestations in the poems of the ruins and wine by presenting different models of the two poets. This study revealed many results, the most important of which are: the acquisition of the ruins and wine symbolism of their meaning expressed by the two poets with subjective meanings that conceal hidden secrets, creative visions - and aesthetic horizons. And the ability to charge the language, so the poetic images were overwhelming with the imagination that provided them with suggestive energy.
امرؤ القيس وابونواس أنموذجا
Keywords: الطّلل، المقدمة الطللية، العصر الجاهلي، امرؤ القيس الخمر، المقدمة الخمرية، العصر العباسي، أبو نواس; Ruins, the introduction of the ruins, the pre-Islamic era, Imru' al-Qais. - Wine, wine introduction, Abbasid era, Abu Nawas